Carotenoids intake by the Portuguese population based on a Total Diet Study approach - Dias, Maria da Graça (2020)
Total Diet Studies (TDS) are a Public Health tool used to determine population exposure to beneficial and harmful chemicals through diet by analysing foods as consumed.